The development, paradigm and academic values of enterprise anthropology—the “fourth revolution” of anthropology - Zhuo Wang (International Journal of Anthropology and Ethnology, 2022)
Abstract As an emerging interdisciplinary field in anthropology, enterprise anthropology (EA) has experienced five historical stages of development since its inception in the 1930s. 2008 marked the first year of internationalized enterprise anthropology, thus prompting the “fourth revolution” of anthropology. Since then, the sub-discipline of enterprise anthropology has entered its fifth stage of development. This stage of enterprise anthropology has witnessed new research subjects, concepts, and theories. Breakthroughs have been made in theoretical research and methodological innovation, and a unique paradigm has been established. In terms of discipline and era, the fifth stage is characterized by: innovative transformation and creative development, integration of Chinese and Western channels for anthropology research, building of international academic networks, and the practice of “people-centered” research. As a result, this stage of enterprise anthropology holds profound theoretical and practical significance for interdisciplinary and academic equity, new ideas and methods for studying the transformation of Chinese society, and establishment of an internationalized research paradigm for the Chinese academic community.